SOME PROBLEMS OF MODERN LABOR MARKET IN RUSSIA - А. R. Akmaldinova (Russian Journal of Economics and Law)
The questions of employment of the population, and the status of the labor market in recent time are discussed in the article. The main problems existing on the part of the formation of the labor market in Russia are analyzed. All the possible directions of employment of regulation and labor market of the country are given in the article.